2018
DOI: 10.1088/1361-6560/aab0f3
|View full text |Cite
|
Sign up to set email alerts
|

Lesion detection and quantification performance of the Tachyon-I time-of-flight PET scanner: phantom and human studies

Abstract: The first generation Tachyon PET (Tachyon-I) is a demonstration single-ring PET scanner that reaches a coincidence timing resolution of 314 ps using LSO scintillator crystals coupled to conventional photomultiplier tubes. The objective of this study was to quantify the improvement in both lesion detection and quantification performance resulting from the improved time-of-flight (TOF) capability of the Tachyon-I scanner. We developed a quantitative TOF image reconstruction method for the Tachyon-I and evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Two TOF resolutions (500 ps and 320 ps) and two DOI resolutions (10 mm and 4 mm) were simulated and compared with the non-TOF and no DOI scanners. The 500 ps TOF was commonly available in commercial PET scanners (Jakoby et al 2011) and 320 ps TOF has also been reported in recent published work (Peng et al 2015, Miller et al 2015, Zhang et al 2018a). The choice of DOI resolutions also covered the range that had been reported in the literature (Du et al 2018, Zhang et al 2013a, Zhang et al 2013b).…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Two TOF resolutions (500 ps and 320 ps) and two DOI resolutions (10 mm and 4 mm) were simulated and compared with the non-TOF and no DOI scanners. The 500 ps TOF was commonly available in commercial PET scanners (Jakoby et al 2011) and 320 ps TOF has also been reported in recent published work (Peng et al 2015, Miller et al 2015, Zhang et al 2018a). The choice of DOI resolutions also covered the range that had been reported in the literature (Du et al 2018, Zhang et al 2013a, Zhang et al 2013b).…”
Section: Methodsmentioning
confidence: 89%
“…However, the image quality of PET is mainly limited by the number of coincidence photon pairs that are recorded in each PET scan due to low sensitivity and concerns regarding radiation dose. To overcome the limitation of current PET scanners and explore new applications of PET, we are building a 2-meter long PET scanner, called the EXPLORER (http://explorer.ucdavis.edu) that will dramatically improve the photon detection efficiency for long axial FOV (AFOV) scans (Badawi et al 2013, Cherry et al 2017, Badawi et al 2018, Zhang et al 2018b). In addition to the improved sensitivity, it can cover the entire human body and will provide total-body high temporal resolution dynamic PET scans for the first time (Zhang et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Several excellent review articles on the current state of the field focus mostly on iterative methods and on needed corrections to the data (attenuation, scatter, random events, detector efficiency, noncolinearity, patient motion, K). See Budinger et al (1978, Tomitani (1981), Budinger (1983), Kao (2008), Li et al (2015), Yu et al (2015), Li et al (2016), Cherry et al (2018), Zhang et al (2018), Zhang et al (2020), Tong et al (2010), Iriarte et al (2016), Gullberg et al (2010), Surti and Karp (2016), Zhang et al (2017Zhang et al ( ), pp. 2465Zhang et al ( -2485, Jones and Townsend (2017), see their section 6 on reconstruction algorithms), and Vandenberghe et al (2016).…”
Section: Relation Of Krnl3d and Krnl3d-tof To Previous Analytical Met...mentioning
confidence: 99%
“…Timeof-flight (TOF) PET scanners can enhance the diagnostic accuracy of reconstructed images by locating positron emissions and improving the signal-to-noise ratio (SNR) of PET data [6,7]. It has been verified that an improved image quality of PET scanner can be achieved with a detector design that is capable of measuring TOF information [8][9][10].…”
Section: Introductionmentioning
confidence: 99%